2021
DOI: 10.1155/2021/3897715
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Coexpression Network Analysis in Mouse Livers following Ischemia-Reperfusion and Extensive Hepatectomy

Abstract: In mouse models, the recovery of liver volume is mainly mediated by the proliferation of hepatocytes after partial hepatectomy that is commonly accompanied with ischemia-reperfusion. The identification of differently expressed genes in liver following partial hepatectomy benefits the better understanding of the molecular mechanisms during liver regeneration (LR) with appliable clinical significance. Briefly, studying different gene expression patterns in liver tissues collected from the mice group that survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…MEturquoise (0 h) and MEblue (12 h) had the highest correlations with fibrotic liver regeneration, suggesting that the expression of hub genes exhibited the most significant changes in the early stage of liver regeneration. Using an ischemia-reperfusion 85% hepatectomy mouse model and mRNA microarray analysis, Liu et al [38] performed WGCNA and showed that the changes of hub gene expression were most significant during 6-24 h after hepatectomy. Furthermore, Zhu [39] conducted WGCNA based on a rat portal vein ligation model and transcriptome-wide sequencing and revealed that the changes in hub gene expression were most significant at 0 h after operation.…”
Section: Discussionmentioning
confidence: 99%
“…MEturquoise (0 h) and MEblue (12 h) had the highest correlations with fibrotic liver regeneration, suggesting that the expression of hub genes exhibited the most significant changes in the early stage of liver regeneration. Using an ischemia-reperfusion 85% hepatectomy mouse model and mRNA microarray analysis, Liu et al [38] performed WGCNA and showed that the changes of hub gene expression were most significant during 6-24 h after hepatectomy. Furthermore, Zhu [39] conducted WGCNA based on a rat portal vein ligation model and transcriptome-wide sequencing and revealed that the changes in hub gene expression were most significant at 0 h after operation.…”
Section: Discussionmentioning
confidence: 99%